EMPLOYEE HAPPINESS OF OFFICE BOYS/GIRLS IN AN INDONESIAN BUSINESS SCHOOL: A PHENOMENOLOGICAL STUDY - Rifda, Nurin Nabila; Pratama, Andika Putra (Journal of Business and Management, 2018)
Abstract.Every person has the right to have their motivation in their every action that their take, including the decision to take a job. They have their own reason why they willing to take an office boy/girl who has a high workload in physical terms. But even so, an office boy/girl has the right to get their own happiness in their working process. And although their job was one of the job that in the lowest status, they still could do their job while show their smile and throwing a jokes to their co-workers. The researcher purpose in this research was to more explore office boys/girls happiness in their workplace. The author was using phenomenology method as for this research that took a study case in an Indonesian Business School. The researcher used phenomenology for this research with the intention of find out the essence of experiences and increase of happiness level of office boy/girl who work in an Indonesian Business School. At the end, office boy/girl experiences area, and their relationship with other parties had significant impact to their level of happiness. With this study, the author hope that they could increase office boys/gilrs level of happiness.Keywords: Motivation, Experience, Job Stress Level, Relationship, and Level of Happiness.Â Â